Cutaneous Leishmaniasis Vaccination: A Matter of Quality - De Luca, Paula Mello; Macedo, Amanda Beatriz Barreto (Frontiers in Immunology, 2016)
There have been exhaustive efforts to develop an efficient vaccine against Leishmaniasis. Factors like host and parasite genetic characteristics, virulence, epidemiological scenarios and, mainly, diverse immune responses triggered by Leishmania species make the achievement of this aim a complex task. It is already clear that the induction of a Th1, pro-inflammatory response is important in the protection against Leishmania infection. However, many questions must still be answered to fully understand Leishmania immunopathology, especially regarding Leishmania-specific Th1 response induction, regulation and persistence. A large number of Leishmania antigens able to induce pro-inflammatory response have been selected so far, but none of them demonstrated efficiency in protection assays. A possible explanation is that CD4 T cells display marked heterogeneity at a single-cell level especially regarding the production of Th1-defining cytokines and multifunctionality. It has been established in the literature that Th1 cells undergo a differentiation process, which can generate cells with diverse phenotypes and survival capabilities. Despite of that, only a few studies evaluate this heterogenic response and the amount of multifunctional CD4 T cells induced by Leishmania vaccine candidates, missing what can be a crucial point in defining a correlate of protection after vaccination. Moreover, most of the knowledge involving the development of cutaneous Leishmaniasis vaccines comes from the mouse model of infection with L. major, which cannot be fully applied to New World Leishmaniasis. For this reason, the immune response triggered by infection with New World Leishmania species, as well as vaccine candidates, need further studies. In this review, we will reinforce the importance of evaluating the quality of immune response against Leishmania, using a multiparametric analysis in order to understand better this complex host-parasite interaction, discussing the differences in the responses triggered by different New World Leishmania species, as well as the impact on the development of an effective vaccine against cutaneous Leishmaniasis.